Valor del rescate de ríos cuando se vive cerca y lejos. La Cuenca de Atoyac en Puebla, México. - Value of river restoration when living near and far. The Atoyac Basin in Puebla, Mexico - Gloria Soto Montes de Oca; Alfredo Ramírez Fuentes (Tecnología y ciencias del agua, 2019)
On analyzing data from a Contingent Valuation (CV) survey to restore the High Atoyac River Basin in Puebla, Mexico, we found that households obtain differentiated benefits due to their condition of closeness to or distance from the river, which are in turn often associated with conditions of vulnerability to water pollution and poverty. Our approach was to estimate Willingness to Pay (WTP) models for two population groups: those residing nearby and those living farther away. As expected, the bid offered and the household’s income are significant determinants of WTP; however, the remainder of the variables change, denoting that poor people are more concerned about river pollution.